Extraordinary magnetoresistance of laser annealed nano boron deposited on oxidized porous silicon - Narjis Zamil Abdulzahra (Karagandy University of the name of acad. E.A. Buketov, 2023)
This study explores the impact of laser annealing on the electrical and magnetic properties of nano boron deposited on oxidized porous silicon (n-B/PSiO2) and its potential for spintronic applications. The Nd: YAG laser was used at varying energies to anneal the n-B thin films. Increasing the laser energy increased grain size and more ordered grain structures. It also increased surface roughness due to forming new grain boundaries and secondary phases. The electrical properties of the material were also affected by the laser annealing, with an increase in forward and reverse current and an increase in electrical resistivity with increased annealing temperature. The study also found that the magnetoresistance of the material increased with increasing laser temperature, attributed to tunnel injection through the thin silicon dioxide layer, and could be up to 7 times higher than non-annealed n-B/PSiO2 in a magnetic field. The study highlights the importance of controlling materials’ grain size and structure for their physical and electrical properties. In addition, it provides insights into the electronic properties of n-B/PSiO2 and the behavior of charge carriers in a magnetic field.
Keywords: Extraordinary Magnetoresistance; Laser Annealing; Nano Boron/ Oxidized Porous Silicon; Electrical Properties; Magnetic Properties; Spintronic Applications